Man's search for meaning : the classic tribute to hope from the Holocaust / Viktor E. Frankl ; part one translated by Ilse Lach ; preface by Gordon W. Allport ; selected letters, speeches, and essays translated by Helen Pisano. - Frankl, Viktor E. (Viktor Emil), 1905-1997 (Rider, 2011)
In 'Man's Search for Meaning', Dr. Frankl offers an account of his life amid the horrors of the Nazi death camps, chronicling the harrowing experience that led to the discovery of his theory of logotherapy.